2021
DOI: 10.1002/pbc.29096
|View full text |Cite
|
Sign up to set email alerts
|

Treatment age and neurocognitive outcomes following proton beam radiotherapy for pediatric low‐ and intermediate‐grade gliomas

Abstract: The relationship between age and neurocognitive functioning following proton beam radiotherapy (PRT) in low-and intermediate-grade gliomas (LIGG) has yet to be examined. Eighteen LIGG patients treated with PRT were prospectively enrolled and received annual neurocognitive evaluations of perceptual/verbal reasoning, working memory, and processing speed postradiotherapy. The median age at diagnosis was 8.2 years (range 1.0-14.7) and the median age at PRT was 9.9 years (range 4.2-17.0).Patients' neurocognitive pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The most frequent new high-grade neurotoxicity was memory impairment. Even if this is a well-described issue, incidences and methods of reporting differ within the literature [ 37 , 38 , 39 , 40 ]. Latest reviews suggest low incidences after focal PBT [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent new high-grade neurotoxicity was memory impairment. Even if this is a well-described issue, incidences and methods of reporting differ within the literature [ 37 , 38 , 39 , 40 ]. Latest reviews suggest low incidences after focal PBT [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proton-beam radiotherapy can also be considered for these etiologies with comparable outcomes [122][123][124][125]. A recent study with a small cohort of 18 pediatric patients with LGGs showed no significant decline in neurocognitive function after proton radiotherapy [126].…”
Section: Low-grade Glioma and Benign Histologiesmentioning
confidence: 99%